Application of the An-Nafs Muhasabah Method to Students' Spiritual Awareness in Islamic Religious Education Subjects at State Junior High School 2 Baubau - Sagita, Yuni Pratiwi; Ridwan , Muhamad; Rahim, Abdul (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study aims to analyze the implementation of the Muhasabah An-Nafs method in increasing students' spiritual awareness in Islamic Religious Education (PAI) subjects at SMP Negeri 2 Baubau. Amidst the challenges of modernization that can erode spiritual values, the Muhasabah An-Nafs method is applied as a self-reflection strategy to help students evaluate their actions, understand religious teachings better, and strengthen their relationship with Allah SWT. This study uses a qualitative approach with data collection techniques through observation, interviews, documentation, and questionnaires. The results showed that the majority of students who followed this method experienced an increase in spiritual awareness and positive changes in daily behavior. Students felt more able to control their lusts, were more disciplined in worship, and better understood the essence of Islamic teachings. In addition, the role of teachers in guiding students and the use of creative media such as inspirational videos and group discussions have been shown to increase the effectiveness of this method. The conclusion of this study confirms that Muhasabah An-Nafs is an effective method in shaping students' spiritual character. For more optimal results, it is recommended that self-reflection be made a routine habit in the learning process. With consistent support from educators and schools, this method can become an integral part of building students' spiritual and moral awareness in the educational environment.